2022
DOI: 10.3389/fcell.2021.759521
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analyses Reveal Inhibition of Hepatic Adipogenesis and Fat Catabolism in Yak for Adaptation to Forage Shortage During Cold Season

Abstract: Animals have adapted behavioral and physiological strategies to conserve energy during periods of adverse conditions. Hepatic glucose is one such adaptation used by grazing animals. While large vertebrates have been shown to have feed utilization and deposition of nutrients—fluctuations in metabolic rate—little is known about the regulating mechanism that controls hepatic metabolism in yaks under grazing conditions in the cold season. Hence, the objective of this research was to integrate transcriptomic and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Moreover, the high expression of ppar α could result in a decrease of CHO and TG in hepatocytes by regulating its target genes related to lipid metabolism, including cyp7a1 , ldlr , acsl3 , and so on. These results suggested that the down-regulation of ppar α induced by OPEs in the present study was probably attributed to the increased TG and CHO in silver carp. Additionally, Acsl catalyzes the synthesis of fatty acyl-CoA thioesters, which are eventually used for the production of membrane lipids, lipid storage as well as fatty acid metabolism. , Current literature demonstrated that the high transcription of Acsl1 could decrease fatty acid β-oxidation and finally led to the increase in the content of TG. , Therefore, the increased mRNA expression of acsl after exposure to OPEs might contribute to the increased TG levels in the serum of silver carp. Changes in the mRNA transcription levels of certain genes related to lipid metabolism induced by the OPEs were also observed in several previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the high expression of ppar α could result in a decrease of CHO and TG in hepatocytes by regulating its target genes related to lipid metabolism, including cyp7a1 , ldlr , acsl3 , and so on. These results suggested that the down-regulation of ppar α induced by OPEs in the present study was probably attributed to the increased TG and CHO in silver carp. Additionally, Acsl catalyzes the synthesis of fatty acyl-CoA thioesters, which are eventually used for the production of membrane lipids, lipid storage as well as fatty acid metabolism. , Current literature demonstrated that the high transcription of Acsl1 could decrease fatty acid β-oxidation and finally led to the increase in the content of TG. , Therefore, the increased mRNA expression of acsl after exposure to OPEs might contribute to the increased TG levels in the serum of silver carp. Changes in the mRNA transcription levels of certain genes related to lipid metabolism induced by the OPEs were also observed in several previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 Current literature demonstrated that the high transcription of Acsl1 could decrease fatty acid β-oxidation and finally led to the increase in the content of TG. 55,56 Therefore, the increased mRNA expression of acsl after exposure to OPEs might contribute to the increased TG levels in the serum of silver carp. Changes in the mRNA transcription levels of certain genes related to lipid metabolism induced by the OPEs were also observed in several previous studies.…”
Section: Opes-induced Changes In Hepatic Lipidmentioning
confidence: 99%
“…Previous studies have reported that peroxisome proliferator-activated receptor (PPAR), a steroid hormone receptor, is highly expressed in the liver and regulates intracellular lipid metabolism [ 31 ]. High-altitude animals are able to reduce lipid synthesis by inhibiting the PPAR signaling pathway, thus maintaining the energy homeostasis of the organism [ 32 , 33 ]. Quantitative proteomics showed that the “PPAR signaling pathway” was significantly enriched in three Tibetan pig liver KEGG pathways ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR signaling pathway was significantly related to lipid metabolism, adipocyte differentiation, gluconeogenesis, and so forth. 54,55 HIF-1 was a transcriptional activator that mediated cellular adaptation to hypoxia. HIF-1 pathway was involved in anaerobic metabolism and tumor progression, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…PPARs had three subtypes (PPARα, PPARβ, and PPARγ). PPAR signaling pathway was significantly related to lipid metabolism, adipocyte differentiation, gluconeogenesis, and so forth 54,55 . HIF‐1 was a transcriptional activator that mediated cellular adaptation to hypoxia.…”
Section: Discussionmentioning
confidence: 99%